ENTERPRISE ARCHITECTURE SYSTEM IN PRIVATE VOCATIONAL SCHOOL USING TOGAF ADM (CASE STUDY OF SMK Al-HIKMAH) - Ridwan Setiawan; Muhammad Rikza Nashrulloh; Reski Ramadhani; Ade Sutedi (Jurnal Teknik Informatika (Jutif), 2022)
Nowadays, the utilization of Information Technology has become the breadwinner or the main power in supporting the business processes of an organization, including educational organizations. The information technology utilization in the education sector, especially at Private Vocational High School (SMK) Al-Hikmah Tarogong Kaler, has not fully followed the current development where the application used in supporting the current activities has not been integrated between one field and another. This case provides the impact on the ineffectiveness of data redundancy because of the difficulty in accessing data and information between fields. Moreover, the use of unplanned systems in the master plan of system development (blueprint) can cause vulnerability to system disassembly which can also be caused by differences in data structure and system platform. The purpose of this study is to design the school's information system enterprise architecture. Besides, this research also aimed to create an enterprise system blueprint for Al-Hikmah Vocational High School. The method used in this study is The Open Group Architecture Framework Architecture Development Method (TOGAF ADM) and it is restricted only into the Migration Planning phase, and the budget for development is not discussed. The study reveals that the information systems and technology blueprints are compiled into the list of system needs and the needs in the form of application candidates for each business process are arranged based on priority needs